2018
DOI: 10.4102/sajpsychiatry.v24i0.1124
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic medication non-adherence among schizophrenia patients in Central Ethiopia

Abstract: BackgroundDespite the fact that adherence to antipsychotic medications is the cornerstone in the treatment and prevention of relapse of the disease, non-adherence is a major problem among schizophrenia patients. The purpose of this study was to assess the magnitude and factors associated with antipsychotic medication non-adherence among schizophrenia patients in Amanuel Mental Specialized Hospital.MethodAn institution-based cross-sectional study was conducted among 412 people with schizophrenia at Amanuel Ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 28 publications
4
22
1
1
Order By: Relevance
“…Khat chewers were also more likely is could be explained by the reason that chewing khat is associated with loss of appetite [34] and the economic burden of buying khat may not allow them to afford healthy diets. e negative effect of khat chewing on adherence was shown by other studies [35,36]. Social support was also significantly associated with adherence to dietary recommendations (AOR: 2.4, 95% CI [1.42-4.35]).…”
Section: Predictors Of Nonadherence To Dietary Recommendationssupporting
confidence: 51%
“…Khat chewers were also more likely is could be explained by the reason that chewing khat is associated with loss of appetite [34] and the economic burden of buying khat may not allow them to afford healthy diets. e negative effect of khat chewing on adherence was shown by other studies [35,36]. Social support was also significantly associated with adherence to dietary recommendations (AOR: 2.4, 95% CI [1.42-4.35]).…”
Section: Predictors Of Nonadherence To Dietary Recommendationssupporting
confidence: 51%
“…In this study, one in three of the study participants were found to be non-adherent to their treatment regimens. This is more or less similar to a finding reported in a review of similar studies (40.5%) published in 2002 [5] and other latest studies conducted elsewhere [6,15,29] but lower than some studies reported in Ethiopia (48.4%) [22], Nigeria (51.7%) [16], Kenya (60.4) [21] and Egypt (74%) [30]. On the other hand, lower rates of nonadherence than the present finding were reported in Latin American community-dwelling (19.8%) [31] and northern Ethiopia (26.5%) [17].…”
Section: Discussionsupporting
confidence: 93%
“…In a recent study, 62 the non-adherence rate was 41.0% among schizophrenia patients, in which APP was found to increase the risk of non-adherence approximately twice as much compared to those with APM. There have been some debates about whether the number of APs are directly associated with poor adherence, however, a number of studies have clearly indicated that APP is strongly associated with increased risk of diverse SEs leading to poor adherence and persistence.…”
Section: What Concerns Should We Have In the Use Of App In Routine Prmentioning
confidence: 92%